Exploring the Pangasinan-Cordillera connection the Pangasinenses and the Ibalois - Fernandez, Erwin S. (2009)
The history of ancient Pangasinan peoples is yet to be written. Rosario Cortes has written what has been regarded as groundbreaking narrative of Pangasinan history consisting of three volumes (1974, 1990a, 1990b). Nonetheless, its chapter on the period before 1572, titled "Prehispanic Culture," is rather sketchy and draws much of the data from the work of Diego Aduarte who was more interested in recording the successes of the Dominican missionary efforts to convert the stubborn Pangasinenses than in noting the latter's customs and traditions.

Recent scholarship, ranging from linguistic to anthropological and folkloric materials, has yielded significant amount of new insights on the culture and history of the Pangasinenses before Spanish colonization. In 1962 Keesing came out with his book on the ethnohistory of the peoples of Northern Luzon, including the people of Pangasinan. Surprisingly, Cortes did not consult this seminal work when she wrote her history of Pangasinan. She could have produced a more credible account on the Pangasinenses if she had included in the picture the relationship between the Cordilleran and lowland peoples. Though she tried to "uncover the beginnings of the Pangasinanes as a people" (1974, ix), her account was circumscribed by the limited resources that she used.
Keywords: Ibaloi (Philippine people); Pangasinan -- History